Pesantren-Based Character Education: The Dzuriyah Strategy in Shaping the Character of Santri Ndalem - Fatah, Muhammad; Khoiruddin, M. Arif; Fakhruddin, Fathiyah Mohd (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
This study aims to analyze the core character values and formation strategies implemented by dzuriyah (descendants of the founders) in shaping the character of santri ndalem (resident student-assistants) at Pondok Pesantren Lirboyo HM Al-Mahrusiyah. Using a qualitative case study approach, data were collected through in-depth interviews, participatory observation, and documentation. The findings reveal that key character values instilled include tafaqquh fi ad-din (deep religious understanding), honesty, responsibility, discipline, and independence. These values are internalized through daily acts of service, emotional closeness, and consistent spiritual practice. The character-building strategies consist of habitual training, role modeling, situational advice, and spiritual reinforcement through prayer. The relationship between dzuriyah and santri ndalem resembles a familial bond that fosters a holistic and humanistic learning environment. Challenges include role conflict between academic obligations and service duties, as well as cultural diversity among students. Despite its single-site limitation, this study contributes conceptually to the development of community-based and spiritually grounded character education in Islamic boarding schools, aligning with Global Citizenship Education values of empathy, tolerance, and moral responsibility.